AB0958 Tendon's Involvement in Marfan Syndrome: Ultrasound Evaluation. (10th June 2014) - Melchiorre, D.; Pratelli, E.; Torricelli, E.; Sofi, F.; Abbate, R.; Matucci-Cerinic, M.; Gensini, G.; Pepe, G.
Abstract : Background: Hypermobility, dislocations and contractures of joints represent overlapping clinical manifestations between rheumatological diseases, neuromuscular disorders and inherited connective tissue disorders such as Marfan Syndrome. Some Authors (1) focused on the muscle alterations responsible for joint hypermobility and dislocations. Ultrasound (US) imaging, and more recently Power Doppler (PD) technology, are regarded as a helpful method to detect myopathic muscle highlights as muscle atrophy, intramuscular fibrosis and fatty infiltration; and tendon structure as tendon abnormalities with a good reproducibility. Objectives: The involvement of the musculoskeletal system with other mild pleiotropic manifestations represents a major criterion in Marfan Syndrome. We aim to investigate by US, the nature, muscular or tendineous, of the contractures present in the hands and feet of a group of Marfan patients. Methods: In 13 Marfan patients previously investigated, an accurate clinical examination was performed. In particular it involved the characterization of muscle skeleton system by visual analogic scale to measure muscle pain (VAS) and muscle strength (MRC system); Beighton scale score to evaluate articular hypermobility; tendon ultrasound to detect deep-superficial flexor and extensor tendon structures of both hands and feet fingers in static and dynamic positions. US exam was carried out by equipments Esaote myLab 70 with linear probe (10-18 MHz; Esaote Genoa - Italy). The probe was oriented perpendicular to its longitudinal axis. Results: Our results showed a reduction of the thickness of all tendons in pts vs controls (p<0.02 for long and short flexor tendons of feet and p<0.0001 for the other tendons). A severe hypoechointensity of these tendons was also detected. The mean value of the area of all tendons was 1 mm 2 among patients and 4 mm 2 among controls. PD was negative in all tendons. No tears of tendon fibers were present. The intra-observed (kappa=0.97) agreement was assessed at baseline and after 1 month. Conclusions: This study reveals the involvement of tendons, unsuspected until now, in the finger contractures alterations observed in all patients. In our patients, all tendons showed hypoechointensity and decreased tendon thickness that can correlate with the alterations in patients with inherited connective tissue disorders. Our original findings suggest an overlapping with chronic inflammatory diseases; the evaluation of biochemical markers are required to address this question. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5950